Professional preparation and training of teachers - selected issues - Khruzd-Matushchyk Alisa (Borys Grinchenko Kyiv Metropolitan University, 2017)
The subject of teachers' professional training and improvement requires particular care and attention, it provides inspiration to think over the current potentialities of teachers' professional development and preparing them for work. Becoming a good educator requires time, which is not the most important factor of professional development. During university studies and over the consecutive years of their professional work, teachers collect experiences. However, their workshop should not be constructed only on the basis of experience. Professional teacher training is the field owing to which teachers supplement their knowledge and acquire new skills, indispensable in the dynamic and demanding work of an educator. What is undertaken in this study are the issues of functioning in the teacher's profession - from educating university students to the challenges of professional work. The article consists of several parts. The first is dedicated to the educating of teachers, the next to the significance of teaching internships in the process of preparing for professional work. The third part comprises the characterization of some selected fields of teacher training and different possibilities of developing professional and personal competences are indicated here. The study is completed with a recapitulation.